2009
DOI: 10.1128/mcb.01864-08
|View full text |Cite
|
Sign up to set email alerts
|

Roles of CLOCK Phosphorylation in Suppression of E-Box-Dependent Transcription

Abstract: In mammalian circadian clockwork, the CLOCK-BMAL1 heterodimer activates E-box-dependent transcription, while its activity is suppressed by circadian binding with negative regulators, such as CRYs. Here, we found that the CLOCK protein is kept mostly in the phosphorylated form throughout the day and is partly hyperphosphorylated in the suppression phase of E-box-dependent transcription in the mouse liver and NIH 3T3 cells. Coexpression of CRY2 in NIH 3T3 cells inhibited the phosphorylation of CLOCK, whereas CIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
162
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(171 citation statements)
references
References 65 publications
8
162
1
Order By: Relevance
“…It has been reported that three of the four serine residues (CLOCK Ser38, Ser42 and BMAL1 Ser90) can Table S1 for full-length DNA used in ITC measurements. be phosphorylated in vivo [38,39]. However, BMAL1 Ser78 is also very likely to undergo phosphorylation predicted by NetPhos 2.0 Server [40], which is supported by the finding of a mass spectrometry record of phosphorylated BMAL1 Ser78 in PhosphoSite database [41].…”
Section: Potential Phosphorylation Sites In Basic Regionssupporting
confidence: 49%
See 1 more Smart Citation
“…It has been reported that three of the four serine residues (CLOCK Ser38, Ser42 and BMAL1 Ser90) can Table S1 for full-length DNA used in ITC measurements. be phosphorylated in vivo [38,39]. However, BMAL1 Ser78 is also very likely to undergo phosphorylation predicted by NetPhos 2.0 Server [40], which is supported by the finding of a mass spectrometry record of phosphorylated BMAL1 Ser78 in PhosphoSite database [41].…”
Section: Potential Phosphorylation Sites In Basic Regionssupporting
confidence: 49%
“…We have shown that the S78E mutant of BMAL1 significantly compromises the ability of DNA binding as well as the transcriptional activity of the complex in cells. Compared with the previously reported inhibitory phosphorylation sites in CLOCK basic regions (Ser38 and Ser42) [38], phosphorylation on BMAL1 Ser78 will be more crucial and efficient in downregulating the transcriptional activity of CLOCK-BMAL1. Considering that many kinases can phosphorylate and regulate the activity of BMAL1 at multiple sites [6,46,47], we propose that BMAL1 Ser78 should be a key residue mediating input signal-regulated transcriptional inhibition for external cues to entrain the circadian clock by kinase cascade.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, it is conceivable that melatonin-induced activation of protein kinase C could ultimately affect CLOCK and BMAL1 to suppress the Clock mutation. Recent work has shown that phosphorylation of CLOCKΔ19 mutant protein is reduced relative to wildtype CLOCK, leading to its stabilization (42). Thus, melatonin could differentially affect CLOCKΔ19 phosphorylation to rescue this defect, which could explain at least in part the selective suppression of the Clock mutant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed functions of other post-translational modifications of clock proteins have been reviewed elsewhere. 6,33,34) In mammals, the core circadian regulator CLOCK has intrinsic histone acetyltransferase (HAT) activity 35) that it uses to acetylate its heterodimeric partner BMAL1. 36) This CLOCK-mediated acetylation increases the interaction of the CLOCK:BMAL1 complex with CRY1, providing another level of control in the circadian negative feedback loop.…”
Section: Possible Crosstalk Between the Circadian Clock And Cellular mentioning
confidence: 99%